On the Feasibility of Developing Current Cost Information. - Corbin, Donald A. (The Accounting Review, 1967)
The article seeks to state a few provocative thoughts that may result in some stimulating and, hopefully, instructive ideas on this important topic. Scholarly interest in what the American Accounting Association calls "basic accounting theory" and one's own needs as a part-time investment analyst have led the author to continuing consideration of the feasibility of getting current-cost information for financial reports. Many accountants view getting current costs as a difficult, non-objective task. The author's first thought on the subject, however, is that there really is no need for discussion: simply use current practices for determining "market" under the lower of cost or market rule. Seriously, perhaps the main reason for discussing the controversial topic of current costs is that in the decade of the Sixties has had some important authoritative statements supporting the essential ideas of many thinkers. The goal of objectivity is an important one, but it is far from being achieved. For example, when a client's new auditor follows another auditor, he does not really find depreciation, bad debts, amortization of development costs, factory overhead allocations, and the like to be objective determinations.